PERAN METODE PERSONAL SELLING TERHADAP PENJUALAN PAKET WISATA DI PT RAYNIZA SUMBER ANUGRAH - , NADIA AZALIA LISTION ([Yogyakarta] : Universitas Gadjah Mada, 2014)
An increase in the number of tourists who travel tours automatically tour operators and travel agents are required to improve the quality of service. The company must still make an effort to improve the quality of sales with the principles put forward there. Purpose of writing this final duty is to know role method personal selling against sales tour packages PT Rayniza Sumber Anugrah to have quality good service by applying standard operating procedures, identifies factors that can succeed a method of selling in PT Rayniza Sumber Anugrah, personal and identify the efforts made to the sale of tour packages with a method of personal the selling could increase. The existence of different data in company can be integrated in a specified period.Data done during the period may 1 up to june 18 2014, data has been obtained in analysis in descriptive. Standard operating procedures are a guide or reference to performing the duties of a job in accordance with its function. The standard operating PT Rayniza Sumber Anugrah form of a timing, matter carried, basic knowledge, responsibility products, and quality control. PT Rayniza Sumber Anugrah has done morein efforts to personal sales method of selling can be intensified. Sales with personal selling methods have an important role for the amount of the sale of package tours in PT Rayniza Sumber Anugrah.